Oral treatment of clindamycin and ciprofloxacin vs intramuscular ceftriaxone and oral doxycycline t outpatient treatment of mild to moderate pelvic inflammatory disease in two hospitals in Lima - Díaz, Víctor (2015)
DESIGN: This multicentric prospective, double-blind study compared the safety and efficacy of clindamvcin and ciprofloxacin versus ceftriaxone and doxycycline in the treatment of outpatients wild mild to moderate pelvic inflammatory disease, diagnosed through laparoscopy. MATERIAL AND METHODS: Prior to the treatment, samples were taken from endocervix, endometrium, abdominal cavity, and in cases with positive cultures to aerobes and anaerohes, Neisseria gonorrhoeae and Chlamydia trachomatis. From the total of 65 patients enrolled, 63 were evaluated for efficacy. RESULTS: The prevalent bacteriae were staphylococcus and streptococcus (among aerobes) and peptostreptococcus and bacteroids (among anaerobes). N. gonorrhoeae was present in 1, 8% (1) of the 53 evaluable patients and c. trachomatis in 9,4% (5). Clinical cure was 85,7% (24 from 28) in the clindamycin plus ciprofloxacin group and 68% (17 from 25) in the ceftriaxone plus doxycycline group. CONCLUSIONS: Both treatment regimens for outpatients with, mild to moderate PID were similar in effectivity and safety.